Assessment of Thyroid Stiffness and Viscosity in Autoimmune Thyroiditis Using Novel Ultrasound-Based Techniques - Dana Stoian; Andreea Borlea; Ioan Sporea; Alexandru Popa; Luciana Moisa-Luca; Alina Popescu (Biomedicines, 2023)
The estimation of viscosity by measuring the shear-wave dispersion (SWD) using ultrasound 2D shear-wave elastography (SWE) is becoming more and more popular. Recent research suggests that SWD can be used in addition to 2D-SWE (shear-wave speed) to diagnose diffuse liver disease. Viscosity was studied for the assessment of normal thyroid tissue. This study aims to evaluate the use of viscosity measurements in patients with chronic autoimmune thyroiditis using the SuperSonic MACH®30 ultrasound machine (Hologic SuperSonic Imagine, Aix-en-Provence, France) which provides the Vi PLUS mode for viscosity and the 2D SWE PLUS mode for shear-wave speed measurements. Valid measurements were obtained in 308 cases, 153 with chronic autoimmune thyroiditis (CAT) and 155 with no thyroid pathology (95.95% feasibility of the methods). The differences between the healthy group and the CAT group were statistically significant both for Vi PLUS (2.5 ± 0.4 vs. 2.8 ± 0.5, p < 0.0001) and for 2D-SWE PLUS (13.5 ± 3.3 vs. 23.1 ± 8.3, p < 0.0001). The diagnostic performance was poor for Vi PLUS alone (AUC = 0.69; cut-off > 2.5 Pa·s, se = 68.6%; sp = 64.52%) and good for 2D-SWE PLUS alone (AUC = 0.861; cut-off > 18.4 kPa, se = 69.9%; sp = 92.2%). Vi PLUS correlated with 2D-SWE PLUS, with the presence of CAT, the thyroid volume, levothyroxine replacement therapy and age. Statistically significant differences were found between the CAT subgroup receiving thyroid replacement therapy and the subgroup without therapy: 24.74 ± 8.33 vs. 21.93 ± 8.12 kPa for 2D-SWE (p = 0.0380) and 3 ± 0.5 vs. 2.7 ± 0.4 Pa·s for Vi PLUS (p = 0.0193). Elastography-based methods improve the classic ultrasound evaluation: 2D-SWE PLUS performed somewhat better in distinguishing CAT from normal thyroid tissue, while Vi PLUS made a slightly better assessment regarding the functional status.